Les helminthes parasites du rouget de roche Mullus Surmuletus (linée, 1758) dans le littoral Est Algérien (Golf d’Annaba) - Gueddoum Raounak; Guidoum Amina (My University, 2022)
The objective of this study is to qualitatively and quantitatively determine the helminth communities identified by the study of parasitic diversity in the host species Mullus surmulutes and to describe the epidemiological parameters by calculating parasitic indices. The composition of the parasitic fauna was determined from the examination of 37 red mullet fish M. surmulutes during the period from March to April 2022, in Annaba Bay in eastern Algeria. 147 parasites were collected belonging to the various systematic groups: Three species of nematodes Hysterothylacium sp, Hysterothylacium fabri and Ascarophis valentina, one species of acanthocephalus Euzethacanthus simplex, three species of digeneans Opecoeloides furcatus, Poracanthium furcatum, Derogene varicus. The values of the parasitic indices and the use of statistical tests allowed us to highlight the influence of size and sex on the intensity of infestation of this fish. ------------------------------------------------------------------------------------------------------------------------------------ الهدف من هذه الدراسة هو التحديد النوعي والكمي لمجتمعات الديدان الطفيلية التي تم تحديدها من خالل دراسة التنوع الطفيلي في األنواع المضيفة في السمك البوري األحمر وصف المعلمات الوبائية عن طريق حساب المؤشرات الطفيلية. تم تحديد تكوين الحيوانات الطفيلية من فحص 37 سمكة البوري األحمر خالل الفترة من مارس إلى أبريل 2022 ، في خليج عنابة شرق الجزائر. تم جمع 147 طفيليًا تنتمي إلى مجموعات منهجية مختلفة : ثالثة انواع من الديدان االسطوانية : fabri Hysterothylacium sp, Hysterothylacium و Ascarophis valentina و ثالثة انواع من الديدان المسطحة ثنائية العائل : furcatus Opecoelides , latus Derogenes و dollfus Poracanthium و نوع واحد من طفيليات أسطوانية شوكية الرأس : simplex .Euzetacanthus سمحت لنا قيم المؤشرات الطفيلية واستخدام االختبارات اإلحصائية بإبراز تأثير الحجم والجنس على كثافة اإلصابة بهذه السمكة. ----------------------------------------------------------------------------------------------------------------------------- L’objectif de cette étude est de déterminer qualitativement et quantitativement les communautés des helminthes recensées par l’étude de la diversité parasitaire chez l’espèce hôte Mullus surmulutes et de décrire les paramètres épidémiologiques par le calcul des indices parasitaires. La composition de la faune parasitaire à été déterminé a partir de l’examen de 37 poissons rougets M. surmulutes durant la période de mars à avril 2022, dans la baie d’Annaba à l’Est algérien. 147 parasites ont été collectés appartenant aux divers groupes systématiques : Trois espèces de nématodes Hysterothylacium sp, Hysterothylacium fabri et Ascarophis valentina, une espèce d’acanthocephale Euzethacanthus simplex, trois espèces de digénes Opecoeloides furcatus, Poracanthium furcatum, Derogenes varicus. Les valeurs des indices parasitaires et l’utilisation des testes statistiques nous ont permis de mettre en évidence l’influence de taille et de sexe sur l’intensité d’infestation de ce poisson.